Pangako Sa ‘Yo: Kompensasyon sa mga Biktima ng Batas Militar - Domingo, Rodrigo C.; Buenaventura-Mangahas, Fe; Melecio, Rita; Mendoza, Meynardo P.; Diciembre, Roberto; Gomez-Dumpit, Karen (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Proceedings of the second "Marcos Pa Rin!" forum.